Pelatihan Bahasa Inggris Prediction Test-TOEFL Like Section Structure dan Reading Bagi Siswa SMA Kesatrian 2 Semarang - Yogatama, Adiprana (Universitas Semarang, 2022)
SMA Kesatrian 2 Semarang routinely organizes TOEFL English tests for prospective graduates. The Deputy Principal for Curriculum said that currently English is a very important provision for students after graduation. So, it is important to hold a TOEFL test to find out and improve students' English skills. In this activity which was held in early January 2022, the material in the TOEFL test that will be taught in this training is the Structure and Written Expression Section Reading Comprehension Section, namely the ability to understand and solve grammatical questions and reading texts in English, with consideration as advanced training. before and the importance of mastering both skills. In this activity, members of community service provide strategies in solving each problem in the Structure and Reading Section. The USM PKM team uses the lecture method in delivering the material and applies a pre-test and post-test system to evaluate the results of the activities. From the results of the pre-test and post-test, more than 75% of the participants experienced an increase in TOEFL scores. It can be concluded that the purpose of this service activity at SMA Kesatrian 2 Semarang was achieved. The material that we convey is very encouraging, new knowledge and understanding about the TOEFL test.Keywords: TOEFL, structure, reading